Effect of smoking status on inhibin‐A in second‐trimester prenatal screening for Down syndrome. (4th February 2014) - Huttly, Wayne; Bestwick, Jonathan; Wald, Nicholas
<x xml:space="preserve">Abstract</x> What's already known about this topic? Inhibin‐A is a useful marker in screening for Down syndrome in the second trimester of pregnancy. It is known to be about 50% higher among women who state they smoke compared with women who state they do not smoke. A single adjustment factor has been used in antenatal screening programmes. What does this study add? This study shows that the extent of the effect of smoking on Inhibin‐A is dependent on the gestational age of the pregnancy. The extent of the effect increases from about 20% higher at early gestation (14 weeks) to about 70% higher at later gestations (20 weeks). An equation allowing the effect of gestation to be considered is presented.